The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0034-7612170582
|View full text |Cite
|
Sign up to set email alerts
|

O uso da tecnologia da informação e comunicação para caracterizar os municípios: quem são e o que precisam para desenvolver ações de governo eletrônico e smart city

Abstract: Resumo Este estudo explora as características de infraestrutura e uso das tecnologias da informação e comunicação dos municípios brasileiros, refletindo sobre a possibilidade de desenvolverem ações de governo eletrônico e smart cities. Um estudo quantitativo de análise de agrupamentos foi realizado sobre dados da Munic 2014 e identificou quatro clusters: o Sem-tecnologia, o Atento ao cidadão, o Atento à legislação e o Provido de TIC, que sugerem diferentes vias de ação em TIC. Cada grupo de municípios apresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
0
10
0
13
Order By: Relevance
“…Blockchain is a technology that can provide security in the storage and management of public data, thus enabling the justification of its adoption. Przeybilovicz, Cunha and Meirelles (2018), when dealing with the use of Information and Communication Technologies (ICT) for the development of e-Government, identified that it is needed to consider the legal and socioeconomic context in which this implementation is being carried out, considering the actors involved and the institutional capacity of the participating bodies. Also, the need to educate citizens in the use of technologies must be considered, facilitating practices of digital democracy.…”
Section: Technologicalmentioning
confidence: 99%
“…Blockchain is a technology that can provide security in the storage and management of public data, thus enabling the justification of its adoption. Przeybilovicz, Cunha and Meirelles (2018), when dealing with the use of Information and Communication Technologies (ICT) for the development of e-Government, identified that it is needed to consider the legal and socioeconomic context in which this implementation is being carried out, considering the actors involved and the institutional capacity of the participating bodies. Also, the need to educate citizens in the use of technologies must be considered, facilitating practices of digital democracy.…”
Section: Technologicalmentioning
confidence: 99%
“…One of the ways to stimulate this process involves the creation of a collaborative environment between government and citizens (Lemos, 2013). For Przeybilovicz, Cunha and Meirelles (2018) cities with a focus on smart governance understand that truly smart involves incorporating collaboration. Pereira, Cunha, Lampoltshammer, Parycek and Testa (2017) discuss some principles of this collaboration, highlighting the theme of smart governance, which implies several stakeholders engaged in decision-making on public services (Lopes, 2017).…”
Section: Coproduction For Community Mobilizationmentioning
confidence: 99%
“…Existing literature have described different forms of citizen participation in models of coproduction of public good (Przeybilovicz, Cunha, & Meirelles, 2018;Salm & Menegasso, 2010), including cities with a focus on intelligent governance (Pereira, Cunha, Lampoltshammer, Parycek, & Testa, 2017). In all these contexts, several actors are responsible for making decisions about public services (Lopes, 2017).…”
Section: The Papersmentioning
confidence: 99%